Membangun Gen-Z yang Berbudaya dengan Berkain-Berkebaya di Kampus UWM Yogyakarta - Dyaloka Puspita Ningrum (Universitas Muhammadiyah Semarang, 2025)
The acceleration of foreign culture has indeed marginalized many people's old habits which are synonymous with the meaning of wisdom, one of which is the use of regional clothing